Purple cabbage (Brassica oleracea L.) cookies as nutraceutical product for Maintaining Healthy Heart - Salsabila Eka Setia Ningrum; Ludy Wiji Lestari; Reza Maulinda Nur Cahya Berlianti; Asyifaul Khasanah; Faza Saiqur Rahmah; Mayu Rahmayanti (World Nutrition Journal, 2023)
Purple cabbage (Brassica oleracea L.) is one of the agricultural products that contain anthocyanins which have the potential as antioxidants. The amount of production in Indonesia is still relatively low due to a lack of consumer demand and a lack of innovation in its utilization. So it is necessary to make new innovations, one of which is by processing it into flour to make Almond Crispy which is then given the name "Ceamond Crispy". The reason Almond Crispy is made, because it is easy to process and can be consumed for a long time. This study aims to determine the anthocyanin compounds contained in processed food "Ceamond Crispy". Almond Crispy is made with a ratio of purple cabbage flour and moderate protein flour in 3 formulations namely formulation 1 (1:2), formulation 2 (1:1), and formulation 3 (2:1). This research was conducted by organoleptic test, anthocyanin, nutritional content. Therefore, it can be concluded that the organoleptic test results obtained brown color, taste like chocolate, vanilla aroma, and crunchy texture. The anthocyanin test results obtained positive results in all three formulations. The results of the nutritional content test showed that the 3 formulations contained the same protein, carbohydrates (starch), and carbohydrates (glucose), but did not contain fat. The results of the preference test showed that formulation 3 was the most preferred formulation. Thus, proving that "Ceamond Crispy" can be received with a positive response by the community and has the potential to be developed into an innovative food that is beneficial for the heart. Thus, proving that "Ceamond Crispy" is safe for consumption by the public and can be developed into innovative foods that are beneficial for heart health.